2008
DOI: 10.1038/ng.268
|View full text |Cite
|
Sign up to set email alerts
|

The lysine demethylase LSD1 (KDM1) is required for maintenance of global DNA methylation

Abstract: Histone methylation and DNA methylation cooperatively regulate chromatin structure and gene activity. How these two systems coordinate with each other remains unclear. Here we study the biological function of lysine-specific demethylase 1 (LSD1, also known as KDM1 and AOF2), which has been shown to demethylate histone H3 on lysine 4 (H3K4) and lysine 9 (H3K9). We show that LSD1 is required for gastrulation during mouse embryogenesis. Notably, targeted deletion of the gene encoding LSD1 (namely, Aof2) in embryo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

30
644
6
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 725 publications
(683 citation statements)
references
References 24 publications
30
644
6
3
Order By: Relevance
“…An alternative mechanism could be that LSD1 can directly demethylate the lysine residues of a maintenance DNMT1 and stabilize it from protein degrading. 20 Interestingly, DNMT1 is frequently upregulated in many types of cancer. Whether LSD1, which is often upregulated in cancer as well, might be partly responsible for overexpression of DNMT1 in cancer remains to be determined.…”
Section: Lsd1/kdm1amentioning
confidence: 99%
“…An alternative mechanism could be that LSD1 can directly demethylate the lysine residues of a maintenance DNMT1 and stabilize it from protein degrading. 20 Interestingly, DNMT1 is frequently upregulated in many types of cancer. Whether LSD1, which is often upregulated in cancer as well, might be partly responsible for overexpression of DNMT1 in cancer remains to be determined.…”
Section: Lsd1/kdm1amentioning
confidence: 99%
“…While di-and trimethylated H3K4 (H3K4me3/2) are so-called 'active chromatin marks' associated with active transcription, di-and trimethylated H3K9 (H3K9me3/2) are denoted transcriptionally 'repressive marks' 9 . We and others have shown that lysine-specific demethylase 1 (Lsd1; also known as Kdm1a, Aof2) selectively removes monoand dimethyl groups from H3K4 or H3K9, thereby causing either repression or activation of gene transcription [13][14][15][16][17][18][19] .…”
mentioning
confidence: 99%
“…Examples include the biotin-dependent assembly of gene repression complexes (Kuroishi et al 2011), the pantothenic acid-dependent generation of acetyl-CoA (Garrett and Grisham 1995) as a substrate for acetylation of histones, the curcumin-dependent inhibition of histone acetyl transferases (Morimoto et al 2008), the niacin-dependent deacetylation of histones by class III histone deacetylases (HDACs) (Boily et al 2008;Dokmanovic et al 2007), the butyrate-and sulforaphane-dependent inhibition of HDACs (Cummings et al 2001;Davie 2003;Ho et al 2009;Myzak et al 2006), the iron-, riboflavin-, and calcium-dependent demethylation of histones (Tsukada et al 2006;Wang et al 2004Wang et al , 2009, and the niacin-dependent poly(ADP phosphorylation) of histones Kim et al 2005;Messner et al 2010). Nutrient-dependent modification of the epigenome is an exciting field of research, because diet is the one environmental factor that the entire population is exposed to on a daily basis during all stages of life, and where exposure can be modified by lifestyle choices.…”
Section: Discussionmentioning
confidence: 99%